Phase 2 trial design of BMS-986278, a lysophosphatidic acid receptor 1 (LPA1) antagonist, in patients with idiopathic pulmonary fibrosis (IPF) or progressive fibrotic interstitial lung disease (PF-ILD). Issue 1 (30th December 2021) - Corte, Tamera J; Lancaster, Lisa; Swigris, Jeffrey J; Maher, Toby M; Goldin, Jonathan G; Palmer, Scott M; Suda, Takafumi; Ogura, Takashi; Minnich, Anne; Zhan, Xiaojiang; Tirucherai, Giridhar S; Elpers, Brandon; et al.
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) and non-IPF, progressive fibrotic interstitial lung diseases (PF-ILD), are associated with a progressive loss of lung function and a poor prognosis. Treatment with antifibrotic agents can slow, but not halt, disease progression, and treatment discontinuation because of adverse events is common. Fibrotic diseases such as these can be mediated by lysophosphatidic acid (LPA), which signals via six LPA receptors (LPA1–6 ). Signalling via LPA1 appears to be fundamental in the pathogenesis of fibrotic diseases. BMS-986278, a second-generation LPA1 antagonist, is currently in phase 2 development as a therapy for IPF and PF-ILD. Methods and analysis: This phase 2, randomised, double-blind, placebo-controlled, parallel-group, international trial will include adults with IPF or PF-ILD. The trial will consist of a 42-day screening period, a 26-week placebo-controlled treatment period, an optional 26-week active-treatment extension period, and a 28-day post-treatment follow-up. Patients in both the IPF (n=240) and PF-ILD (n=120) cohorts will be randomised 1:1:1 to receive 30 mg or 60 mg BMS-986278, or placebo, administered orally two times per day for 26 weeks in the placebo-controlled treatment period. The primary endpoint is rate of change in per cent predicted forced vital capacity from baseline to week 26 in the IPF cohort. Ethics and dissemination: This study will be conducted in accordance with Good Clinical Practice guidelines, Declaration of Helsinki principles, and local ethical and legal requirements. Results will be reported in a peer-reviewed publication. Trial registration number: NCT04308681 .